IMPLEMENTATION OF GAME-BASED LEARNING METHODS ON MULTIPLE AND DIVISION COUNTING OPERATIONS IN CLASS VII SMP PLUS RAUDLATUL MUQORROBIN KALISAT - Utari, Yuli Putri; Triyani, Septi; Panglipur, Indah Rahayu (Journal on Research and Review of Educational Innovation, 2023)
The purpose of this study was to describe and examine the application of game-based learning methods to multiplication and division arithmetic operations. The research was conducted at SMP Plus Raudlatul Muqorrobin Kalisat, Kalisat District, Jember Regency. This type of research is exploratory and qualitative approach. The subjects of this research were class VII students of junior high school. Data collection techniques used interviews with mathematics teachers, observations related to learning activities from mathematics learning materials, multiplication and division operations, and documentation in the form of photographs. The data analysis technique used in this study uses Miles and Huberman's steps, namely data reduction, presentation, and conclusion. The results of the study showed a positive change in the use of game-based learning methods in multiplication and division arithmetic operations. These changes are reflected in the enthusiasm of students while playing, increased student interest in learning, and student learning outcomes. By applying appropriate learning methods, it is necessary to create solutions for students and teachers to facilitate the achievement of learning objectives.